Metabolic interactions underpinning high methane fluxes across terrestrial freshwater wetlands - Emily K. Bechtold; Jared B. Ellenbogen; Jorge A. Villa; Djennyfer K. de Melo Ferreira; Angela M. Oliverio; Joel E. Kostka; Virginia I. Rich; Ruth K. Varner; Sheel Bansal; Eric J. Ward; Gil Bohrer; Mikayla A. Borton; et al. (Nature Communications)
Abstract Current estimates of wetland contributions to the global methane budget carry high uncertainty, particularly in accurately predicting emissions from high methane-emitting wetlands. Microorganisms drive methane cycling, but little is known about their conservation across wetlands. To address this, we integrate 16S rRNA amplicon datasets, metagenomes, metatranscriptomes, and annual methane flux data across 9 wetlands, creating the Multi-Omics for Understanding Climate Change (MUCC) v2.0.0 database. This resource is used to link microbiome composition to function and methane emissions, focusing on methane-cycling microbes and the networks driving carbon decomposition. We identify eight methane-cycling genera shared across wetlands and show wetland-specific metabolic interactions in marshes, revealing low connections between methanogens and methanotrophs in high-emitting wetlands. Methanoregula emerged as a hub methanogen across networks and is a strong predictor of methane flux. In these wetlands it also displays the functional potential for methylotrophic methanogenesis, highlighting the importance of this pathway in these ecosystems. Collectively, our findings illuminate trends between microbial decomposition networks and methane flux while providing an extensive publicly available database to advance future wetland research.